Placental growth factor, pregnancy-associated plasma protein-A, soluble receptor for advanced glycation end products, extracellular newly identified receptor for receptor for advanced glycation end products binding protein and high mobility group box 1 levels in patients with acute kidney injury: a cross sectional study - Zakiyanov, Oskar; Kriha, Vitezslav; Vachek, Jan; Zima, Tomas; Tesar, Vladimir; Kalousova, Marta (BMC nephrology, 2013)
BACKGROUND: Placental growth factor (PlGF), pregnancy-associated plasma protein-A (PAPP-A), soluble receptor for advanced glycation end products (sRAGE), extracellular newly identified receptor for RAGE binding protein (EN-RAGE) and high mobility group box 1 (HMGB-1) are novel biomarkers in chronic kidney disease (CKD). However, their clinical significance in acute kidney injury (AKI) is unknown. The aim of this cross-sectional study was to determine whether selected biomarkers are changed in AKI patients. METHODS: Serum PlGF, PAPP-A, sRAGE, EN-RAGE and HMGB-1 levels were assessed in 40 patients with AKI, 42 CKD 5 patients, 31 haemodialysis patients (HD) and 39 age-matched healthy controls. RESULTS: PAPP-A was elevated in AKI (20.6 ± 16.9 mIU/L) compared with controls (9.1 ± 2.3 mIU/L, p < 0.001). PlGF was not increased in AKI (11.7 ± 7.4 pg/mL) versus controls (8.5 ± 2.4 pg/mL, n.s.), as well as sRAGE was not elevated in AKI (2400 ± 1400 pg/mL) compared with controls (1760 ± 730 pg/mL, n.s), but was lower compared with CKD 5 (3200 ± 1500 pg/mL, p < 0.05); EN-RAGE was elevated in AKI 480 ± 450 ng/mL in comparison with controls (60 ± 62 ng/mL), CKD 5 (190 ± 120 ng/mL), and HD (120 ± 100 ng/mL), all p < 0.001. Similarly, HMGB-1 was increased in AKI (5.8 ± 7.5 ng/mL) versus controls (1.7 ± 1.4 ng/mL), CKD 5 (3.2 ± 3.1 ng/mL) and HD (2.5 ± 2.1 ng/mL), all p < 0.001.In AKI group, in multivariate regression analysis: PAPP-A levels were associated with transferrin (p <0.001), negatively with albumin (p < 0.01) and prealbumin (p < 0.05); PlGF levels were associated with C--reactive protein (p < 0.001). EN-RAGE levels were associated with ferritin (p < 0.01) and orosomucoid (p = 0.02), and HMGB-1 levels with leukocyte count (p < 0.01) and negatively with proteinuria (p = 0.02). CONCLUSIONS: In AKI patients, PAPP-A, EN-RAGE and HMGB1 are elevated, but sRAGE and PlGF are not increased. Whereas PAPP-A correlates with markers of nutrition; PlGF, EN-RAGE and HMGB-1 are related to inflammatory parameters.
Keywords: Pregnancy-Associated Plasma Protein-A; Pregnancy Proteins; Female; Prevalence; akutní poškození ledvin; ženské pohlaví; průřezové studie; Reproducibility of Results; Renal Insufficiency, Chronic; lidé; Receptors, Immunologic; Sensitivity and Specificity; senzitivita a specificita; chronická renální insuficience; protein HMGB1; receptory imunologické; těhotenské proteiny; Middle Aged; Risk Factors; prevalence; reprodukovatelnost výsledků; Cross-Sectional Studies; Czech Republic; rizikové faktory; Česká republika; lidé středního věku; HMGB1 Protein; Acute Kidney Injury; těhotenský plazmatický protein A; Humans